AI Tools in Academic Writing: Indonesian EFL Students' Perspective - Suhail, Ayesha; Nur Alim, Chondro; Valmeo, Christinelle (International Journal of Language Teaching and Education, 2026)
The purpose of this study was to explore Indonesian EFL students’ beliefs and challenges regarding the use of Artificial Intelligence (AI) tools in academic English writing. A mixed-methods approach was employed, involving a descriptive survey of 112 students from the English Education Department at Universitas Muhammadiyah Purwokerto and semi-structured interviews. Quantitative data provided an overview of students’ AI usage patterns, while qualitative data offered deeper insights into their experiences and perceptions. The findings revealed that students generally held positive attitudes toward AI tools and used them for idea generation, grammar checking, vocabulary enhancement, and text organisation. AI tools were also perceived to increase confidence and reduce writing anxiety, supporting both cognitive and affective aspects of learning. However, participants expressed concerns about overreliance on AI, the accuracy and reliability of AI-generated content, issues of originality, and academic integrity. Importantly, students demonstrated awareness of these limitations and emphasised the need for critical evaluation when using AI. The findings highlight the importance of integrating AI literacy into academic writing instruction and establishing clear institutional guidelines for the ethical and responsible use of AI. Overall, AI should be viewed not as a replacement for learners’ efforts but as a supportive tool that can enhance academic writing when used critically and responsibly.